Kebebasan dan hak-hak asasi di bawah perlembagaan persekutuan - satu analisis umum - Abdul Aziz Bari, (Fakulti Undang - Undang, 2000)

(untitled)
The article discusses trends and problems pertaining to the issues of fundamental liberties or human rights under the Federal Constitution of Malaysia. Given this emphasis the article does not provide detailed analyses or reviews of the constitutional provisions, statutes and case law on the issue. Instead the discussion highlights and characterizes the main trends in the statutory and case law and compares them with the ideals and foundations of the Constitution. This means that the problem is not so much about the provisions in the Constitution but rather with their implementation; namely the way the legislation and the court flesh them out in detail. In the process the article attempts to offer some insights over the understanding, commitments and attitudes among members of the Executive, Legislature and Judiciary on human rights. The article also raises issues with SUHAKAM, the newly-established commission on human rights particularly its ability and relevance in the enhancement of human rights provisions. The article argues that most of the basic notions of human rights are of universal nature and dismisses the allegations that they are Western-inspired. The author contends that some of fundamentals are even rooted in the divinely inspired precepts. These are interesting, as modern constitutions are the manifestations of democracy and the ideals of constitutionalism; a character that is essentially secular and worldly. Given the scenario in Malaysia the article proposes a re-education on the subject and, if necessary, a new constitutional settlement, as they are indispensable in the enhancement of human rights provision